The Influence of Learning Interest and learning Motivation on Learning Outcomes in Economic Learning - Mariyana, Weni; Setiawan, Rezi; Sugiyanto, Roso; Asy’arie, Bima Fandi; Fajar, Adam Hafidz Al (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
The purpose of this study was to determine (1) the influence of learning interest in student economic learning. (2) the influence of learning motivation on the learning outcomes of students’ economics subjects. (3) the influence of learning interest, parental attention, and learning motivation together on the learning outcomes of economics subjects. The focus of research was carried out at SMA Negeri 2 Tegineneng, Lampung. This type of research uses verifiative descriptive research, quantitative methods with an “ex post facto and survey” approach. The data collection technique is through observation, questionnaires, and documentation. First, there is a positive and significant influence of learning interest on student economic learning outcomes with a contribution of 0.150 or 15%. This means that a student has a high interest in learning, it is likely that his learning outcomes will increase, and vice versa. Second, there is a positive and significant influence of learning motivation on the learning outcomes of students’ economics subjects with a contribution of 0.379 or 37.9%, this means, if students have high learning motivation, learning outcomes can increase, and vice versa. Third, a positive and significant influence on learning interest, parental attention, and learning motivation together on the learning outcomes of students’ economics subjects with a contribution of 0.379 or 37.9%.